EFEKTIFITAS METODE KOLOSTRUM DAN METODE KASA KERING TERHADAP WAKTU PELEPASAN TALI PUSAT DI BPS NY. ENDANG PURWANINGSIH DAN BPS NY. ISTIQOMAH KECAMATAN RAKIT KABUPATEN BANJARNEGARA TAHUN 2011 - Sofiana, Ika; Agustina, Ely Eko (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2011)
Infections in neonates in Indonesia was still high.  One type of infection that often occurs in neonates are Tetanus Neonatorum.  These infections can occur because the umbilical cord care is not clean. Many studies have shown that the use of colostrum can accelerate umbilical cord separation time, but colostrum is still rarely used to treat the umbilical cord. The method most commonly used is dry gauze. Therefore, researcher wanted to compare the effectiveness of both methods. This study aims to prove the difference in long separation umbilical cord using the method of colostrum compared with dry gauze method. This type of research is a true experiment with the technique of sampling is simple random sampling. Approach time prospectively. The data collection by conducting observations of the newborn. The analysis used is test "t" 2n independent. The study was conducted on 40 infants born with gestational age between 38-42 weeks and birth weight between 2500-4000 g without congenital defects. 20 infants were treated with the method of colostrum and 20 infants treated with dry gauze method. The umbilical cord separation time in infants who were treated using colostrum (94.23 hours)was faster than those treated with dry gauze (128.94 hours).  The differences mean of umbilical cord separation time between the two methods was 34.71 hours.  Fastest time of the umbilical cord separation time in the colostrum group was 54.83 hours and late time is 170.50 hours, whereas the fastest time of the umbilical cord separation on dry gauze group was 77.00 hours and late time was 231.67 hours.  There was a significantly difference of the umbilical cord detachemant time between the treatment groups (p = 0.006). Colostrum can be used effectively and safely to treat the umbilical cord. Key words: umbilical cord separation time, colostrum, dry gauze.